The situationist city - Sadler, Simon (Cambridge Mass. : MIT Press, 1998)
"From 1957 to 1972 the artistic and political movement known as the Situationist International (SI) worked aggressively to subvert the conservative ideology of the Western world. The movement's broadside attack on "establishment" institutions and values left its mark upon the libertarian left, the counterculture, the revolutionary events of 1968, and more recent phenomena from punk to postmodernism. But over time it tended to obscure situationism's own founding principles. In this book, Simon Sadler investigates the artistic, architectural, and cultural theories that were once the foundations of situationist thought, particularly as they applied to the form of the modern city." "According to the situationists, the benign professionalism of architecture and design had led to a sterilization of the world that threatened to wipe out any sense of spontaneity or playfulness. The situationists hankered after the "pioneer spirit" of the modernist period, when new ideas, such as those of Marx, Freud, and Nietzsche, still felt fresh and vital. By the late fifties, movements such as British and American pop art and French nouveau realisme had become intensely interested in everyday life, space, and mass culture. The SI aimed to convert this interest into a revolution at the level of the city itself." "Simon Sadler searches for the situationist city among the detritus of tracts, manifestos, and works of art that the SI left behind. The book is divided into three parts. The first, "The Naked City," outlines the situationist critique of the urban environment as it then existed. The second, "Formulary for a New Urbanism," examines situationist principles for the city and for city living. The third, "A New Babylon," describes actual designs proposed for a situationist city."--Jacket
Acknowledgments -- A note on translations -- Introduction -- The naked city realities of design and space laid bare -- formulary for a new urbanism rethinking the city -- a new babylon the city redesigned -- Conclusions -- Notes -- Bibliography -- Illustration credits -- Index.
Includes bibliographical references (pages 201-207) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International situationniste -- Influence; Architecture -- Philosophy; Avant-garde (Aesthetics) -- Europe -- History -- 20th century; Architecture -- Philosophie; ARCHITECTURE -- Urban & Land Use Planning; Architecture -- Philosophy; Avant-garde (Aesthetics); Influence (Literary, artistic, etc.); Europe; Stedenbouw; Situationisme; 1900-1999; History; Bibliografieën (vorm)